Bow-tie shaped fibulae from the cemetery of Budapest/Aquincum-Graphisoft Park - Sáró, Csilla; Lassányi, Gábor (Dissertationes Archaeologicae, 2020)
The main aim of this paper is the presentation of two rare fibulae from the Eastern Cemetery of the civil town of Budapest/Aquincum. On the former territory of the Óbuda Gas Factory, new parts of the cemetery were excavated during the years 2004–2017 under the direction of G. Lassányi. The fibulae discussed in our study were found in the skeleton grave No. 795. These fibulae have a special form and their type can be defined easily. They belong to a low-numbered fibula type of Pannonia, the bow-tie shaped fibulae.